International pooled study on diet and bladder cancer: the bladder cancer, epidemiology and nutritional determinants (BLEND) study: design and baseline characteristics. Issue 1 (December 2016) - Goossens, Maria; Isa, Fatima; Brinkman, Maree; Mak, David; Reulen, Raoul; Wesselius, Anke; Benhamou, Simone; Bosetti, Cristina; Bueno-de-Mesquita, Bas; Carta, Angela; Allam, Md; Golka, Klaus; et al.
Abstract Background In 2012, more than 400, 000 urinary bladder cancer cases occurred worldwide, making it the 7th most common type of cancer. Although many previous studies focused on the relationship between diet and bladder cancer, the evidence related to specific food items or nutrients that could be involved in the development of bladder cancer remains inconclusive. Dietary components can either be, or be activated into, potential carcinogens through metabolism, or act to prevent carcinogen damage. Methods/design The BLadder cancer, Epidemiology and Nutritional Determinants (BLEND) study was set up with the purpose of collecting individual patient data from observational studies on diet and bladder cancer. In total, data from 11, 261 bladder cancer cases and 675, 532 non-cases from 18 case–control and 6 cohort studies from all over the world were included with the aim to investigate the association between individual food items, nutrients and dietary patterns and risk of developing bladder cancer. Discussion The substantial number of cases included in this study will enable us to provide evidence with large statistical power, for dietary recommendations on the prevention of bladder cancer.